A Figura do Intelectual e a Razão Universal na Fundação do Instituto Histórico e Geográfico Brasileiro - Gonçalves, Sérgio Campos (Brasiliana: Journal for Brazilian Studies, 2013)
Este ensaio apresenta um estudo sobre a articulação da biografia coletiva dos fundadores do Instituto Histórico e Geográfico Brasileiro e de sua Revista com a política cultural do Estado imperial brasileiro, em que se observa, sobretudo, como o perfil dos membros do Instituto conformava determinada figura de intelectual através de sua rede de sociabilidades, sua mentalidade civilizatória e a cultura política de sua geração. O objetivo é evidenciar que o significado do intelectual no contexto da fundação do IHGB se define através de um discurso que une a fala em nome da razão, da humanidade e da civilização, à fala em nome do Estado e da nação. This essay presents a study on the articulation of the collective biography of the Brazilian Historical and Geographical Institute’s founders and of its journal with the cultural politic of the Brazilian emperor state, in which is observed, above all, how the Institute members’ profile fitted certain image of intellectual through its sociability network, its civilizing mentality and the political culture of its generation. The objective is to outline that the meaning of the intellectual in the context of the foundation of the Brazilian Historical and Geographical Institute is defined through a discourse that unify the speech on the behalf of reason, of humanity and of civilization, with the speech on the behalf of the state and of the nation.